Pengaruh proporsi penambahan daun katuk (Sauropus androgynus L. Merr.) terhadap sifat fisiko kimia selai lembaran apel - Eva Nirwana Anwar; Rekna Wahyuni (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2020)
Anna apple jam is defined as an apple jam that is modified into apple jam in sheet form (sheet jam). Apple anna makes it possible as a raw material for making jam sheets because it has high pectin, which is 9-15% and has acidity in accordance with the requirements, which is 3.46. Katuk plant (Sauropus androgynous L.Merr.) has long been known by the people in Indonesia as a vegetable plant with high nutritional content. Flavonoids contained in katuk leaves (Sauropus androgunus (L) Merr) have the ability as a powerful antioxidant. The experimental design used was a randomized block design (RBD) consisting of 1 factor with 5 treatments: K1 (Addition of 0% katuk leaf pulp, 100% apple pulp), K2 (Addition of katuk leaf pulp 5%, 95% apple pulp ), K3 (Addition of katuk leaf pulp 10%, the pulp of apples 90%), K4 (Addition of katuk leaf pulp 15%, 85% apple pulp) and K5 (Addition of katuk leaf pulp 20%, apple pulp 80%). Data obtained after the treatment of the organoleptic test (flavor, taste, texture, and color) on each variable was entered in the table to be analyzed by Friedman Test. Where as in the treatment of physicochemical tests (water content, antioxidants, texture, and color) were analyzed by F test and if there were differences were analyzed by 5% LSD test. The best treatment based on effectiveness index was K2 (addition of katuk leaf pulp 5%, apple pulp 95%) with physicochemical parameter values ​​namely water content (45.69%), antioxidants (96.67 mg/ml), texture (1.17), color b + (7.47) and organoleptic parameter values ​​are taste (4.44), flavor (4), color (4.28), texture (3.76).